The Influence of the Textile Substrate Colour on the Speed of Colour Change of Thermochromic Prints - Katarina Maričić; Nemanja Kašiković; Nada Miketić; Teodora Gvoka; Gordana Bošnjaković (Tehnički Vjesnik, 2024)
This paper aims to examine the influence of the colour of textile materials on the speed of colour change of a screen-printed sample using a reversible thermochromic ink, focusing on application in the sports industry. In other words, what effect the colour of textile materials has on the optical properties of the printed sample during its cooling. Two different types of textile materials of different colours were used as a substrate for printing, and a water-based magenta leuco thermochromic ink with an activation temperature of 31 °C was used for screen printing. Experimental results indicate significant differences in the speed and intensity of colour change between different colours of textile substrates. It has been found that darker substrate colours tend to provide a slower and less intense colour change of the printed pattern compared to lighter substrate colours. These studies are essential for textile designers and sportswear manufacturers to understand better the factors that influence the speed and intensity of colour change due to monitoring the physical and physiological state of the athlete.